PELAKSANAAN PEMBEBASAN BERSYARAT MERUPAKAN BENTUK PEMBINAAN NARAPIDANA DAN HAMBATANNYA DALAM PRAKTEK - Soeharto Soeharto (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTGranting parole to prisoners is the last link of the effort to foster inmte in the correctional system. By means of parole, inmates can improve communication with the public at large, to rediscover her dignity as a human being and existence as a member of society. In the implementation of this should be considered conditional or based on the principles of correctional, one of which stated that during the loss of freedom of movement, inmates must be introduced to the public and may not be exiled from it. By paying attention to one of these principles, it is expected that the implementation of parole as one means to foster inmate in the correctional system is based on achieving goals and objectives. Factors that are inhibitors or hindrance to the implementation of conditional release are as follows: inmates in question still has another case that has not been decided by the courts; inmates concerned has not received a remission or reduction law, inmates are recidivists; inmates concerned during fostered in institutions correctional offenses; criminal inmates who underwent less than one year. Prison officials did want that parole should be increased, but inmates often commit violations while in prison, so that the administrative requirements do not support the proposed inmate to obtain parole. Sometimes the decline in letter parole decision is too late and in case of this sort, the inmates themselves will be confused, while the officer has been tried as much as possible, it could be officers penitentiary inmates feel that complicates the degree. From society’s parole also sometimes get obstacles that make inmates often feel less acceptable, for example, the victim’s family is still resentment against inmates is concerned and there is a presumption of society that these prisoners after coming out and getting parole may disrupt order and security in neighborhood.